Prosecutor as a Subject of Guaranteeing Human Rights in Ukraine - V. V. Chumak (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article has studied the essence of the prosecutor’s activity as a subject of guaranteeing human rights in Ukraine. The peculiarities of the reform of the prosecutor’s office have been emphasized and its relationship with the activity of the prosecutor as a subject of guaranteeing human rights has been determined. A legal framework that regulates the activities of the prosecutor as a subject of guaranteeing human rights has been established. It has been concluded that the state and level of human and civil rights and fundamental freedoms depend on the normative regulation of the prosecutor’s activity as a subject of guaranteeing human rights in Ukraine, which is the cornerstone of Ukraine’s establishment as a state governed by the rule of law with observance of the rule of law.